GENE-09. LONG NONCODING RNA lncHLX2-7 A PUTATIVE MOLECULAR MARKER AND A THERAPEUTIC TARGET FOR GROUP III MEDULLOBLASTOMA. (11th November 2019) - Katsushima, Keisuke; Joshi, Piyush; Lee, Bongyong; Stapleton, Stacie; Jallo, George; Raabe, Eric; Eberhart, Charles; Perera, Ranjan
Abstract: Medulloblastoma (MB), a central nervous system tumor that predominantly affects children, requires aggressive therapy. It can recur as resistant disease and is recurrent medulloblastoma is frequently fatal. There are four groups of MBs (WNT, SHH, Group III, and Group Ⅳ) and they are characterized by specific mutations, copy number alterations, transcriptomic profiles, and clinical outcomes. Recent advances in noncoding RNA genome could contribute to sub-classification of medulloblastoma. The focus of this study is to identify novel long noncoding RNAs (lncRNAs) as molecular markers and potential therapeutic targets within each subgroup of MBs, in particular within the Group III. We analyzed publicly available 723 microarrays and 123 RNA-seq datasets using machine-learning statistical algorithms (random-forest and Lasso) to identify a group of putative lncRNA signatures that may be able to differentiate medulloblastoma subgroups accurately. Among those, lncHLX2-7 was highly upregulated in Group III MBs compared to other groups. RNA-FISH analysis revealed that lncHLX2-7 is highly expressed primarily in Group III MB as compared to other groups and normal brain (cerebellum). Furthermore, depletion of lncHLX2-7 significantly reduced 20- 30% of cell growth together with the induction of apoptosis in MED211 and D425-MED Group III MB cell lines (n=3, p< 0.01, t-test). We present here supporting evidence that lncHLX2-7 is a novel molecular marker and potential therapeutic target for Group III MBs in children.